2017
DOI: 10.1016/j.msea.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

On the microstructure and mechanical property of as-extruded Mg-Gd-Y-Zn alloy with Sr addition

Abstract: In this study, microstructure evolutions of 0.2, 0.6) alloys (named as sample 0Sr, 0.2Sr, 0.6Sr) during heat-treatment and extrusion were investigated. As-cast sample 0Sr contains typical long period stacking ordered (LPSO) phases and Mg 3 RE. With Sr addition, amounts of LPSO phases decrease and are gradually replaced by the Mg 17 Sr 2 phases. After homogenization and annealing treatment, profuse strip LPSO phases readily precipitate in grain interiors of sample 0Sr, while only Mg 17 Sr 2 and Mg 3 RE phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is a structural order and chemical sequence phase where structural ordering refers to the periodic arrangement of atoms along the (0001) α direction while chemical ordering refers to the orderly distribution of RE/Zn atoms on two or four layers of densely packed surfaces (Wang et al , 2008). At present, numerous studies have shown that LPSO can effectively improve the strength and plasticity of magnesium alloys, and thus, introducing LPSO structure into magnesium alloys is one of the most popular strengthening methods (Liu et al , 2017; Xu et al , 2015; Hagihara et al , 2019). Xu et al (2015) studied the formation mechanism and conversion relationship of LPSO structures are contrastively analyzed with magnesium-based alloy, and shown that LPSO structures can significantly improve the strength, ductility of magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…It is a structural order and chemical sequence phase where structural ordering refers to the periodic arrangement of atoms along the (0001) α direction while chemical ordering refers to the orderly distribution of RE/Zn atoms on two or four layers of densely packed surfaces (Wang et al , 2008). At present, numerous studies have shown that LPSO can effectively improve the strength and plasticity of magnesium alloys, and thus, introducing LPSO structure into magnesium alloys is one of the most popular strengthening methods (Liu et al , 2017; Xu et al , 2015; Hagihara et al , 2019). Xu et al (2015) studied the formation mechanism and conversion relationship of LPSO structures are contrastively analyzed with magnesium-based alloy, and shown that LPSO structures can significantly improve the strength, ductility of magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the addition of Sr into the Mg alloys containing LPSO structure may also modify the LPSO structure. In the latest study, the addition of Sr will inhibit the formation of LPSO structure in Mg-6Gd-3Y-0.1Zn alloy [14]. However, this alloy contains very little amount of LPSO structure and the effect of Sr on LPSO structure has not been visualized clearly.…”
Section: Introductionmentioning
confidence: 98%
“…Mg–Zn–Zr alloys are widely used in industrial production due to their excellent strength, plasticity, and corrosion resistance [12]. However, since these alloys are affected by a high zinc content, high hot tearing tendency, and poor heat resistance, researchers have attempted to refine their grains and improve their creep resistance, and casting performance by adding a certain amount of rare-earth elements [13]. Ashrafizadeh et al [14] pointed out that adding Y, Gd, La, and other rare-earth elements to a Mg alloy can improve its fluidity, heat resistance, creep resistance, corrosion resistance, and it can also easily undergo dehydrogenation and oxygenation.…”
Section: Introductionmentioning
confidence: 99%